The effect of non-invasively obtained central blood pressure on cardiovascular outcome in diabetic patients in Assiut University Hospitals - Lobna F. El Toony; Andrew N. Ramzy; Mohamed A. A. Abozaid (SpringerOpen, 2022)
Abstract Background The major cause of morbidity and mortality in diabetes is cardiovascular disease, which is exacerbated by the presence of hypertension. Therefore, proper control of BP in diabetic hypertensive patients is essential. Few studies have specifically investigated the prognostic significance of central BP in Egyptian populations with diabetes and hypertension and its relation with cardiovascular outcome. This study aims to evaluate relation between central BP and diabetic composite cardiovascular complications. Results Diabetic patients with CVD were significantly older (p value < 0.01), obese (p value < 0.01) with long duration of diabetes (p value < 0.001) and had significantly higher peripheral and central systolic and diastolic BP and higher AIx@75(p values < 0.01) than those without CVD. Regarding the metabolic parameters, they had significantly higher fasting blood glucose, HbA1c, and higher blood cholesterol levels (p values < 0.001), higher LDL (p value < 0.01), triglycerides levels (p value = 0.014), and microalbuminuria (p value = 0.028). Logistic regression analysis found increased BMI, central systolic BP, and AIx@75 were independent predictors of composite CVD (p values < 0.05). Conclusions There is a pattern of favorability towards central rather than peripheral BP indices to predict the occurrence of CVD in diabetic patients.